2017
DOI: 10.11113/mjfas.v13n2.652
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of ZSM-5 from kaolin and the influence of organic template

Abstract: We investigated the transformation of kaolin to ZSM-5 using hydrothermal synthesis method and the influence of organic template as a structure-directing agent.  The formation of ZSM-5 from kaolin occurred via dissolution of kaolin to form amorphous silica. Zeolite-like analcime produced when the hydrothermal treatment was extended to 18 h. We found synergistic effect of using a mixture of TPAOH and TPABr organic template to enhance kaolin dissolution, initiate ZSM-5 formation and inhibit the transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…58 Prasetyoko et al have obtained ZSM-5 with 100% relative crystallinity without pretreatment from kaolin containing 8.89 wt% Fe 2 O 3 and many other impurities. 99 Quartz and iron ions are undesirable when zeolites are used as detergents. 3 Kwakye-Awuah et al have shown that zeolite NaY obtained from Anfoega kaolin has lower relative crystallinity than NaY obtained from Awaso Volta kaolin under the same experimental conditions.…”
Section: Kaolin Pretreatment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Prasetyoko et al have obtained ZSM-5 with 100% relative crystallinity without pretreatment from kaolin containing 8.89 wt% Fe 2 O 3 and many other impurities. 99 Quartz and iron ions are undesirable when zeolites are used as detergents. 3 Kwakye-Awuah et al have shown that zeolite NaY obtained from Anfoega kaolin has lower relative crystallinity than NaY obtained from Awaso Volta kaolin under the same experimental conditions.…”
Section: Kaolin Pretreatment Methodsmentioning
confidence: 99%
“…58 Prasetyoko et al have obtained ZSM-5 with 100% relative crystallinity without pretreatment from kaolin containing 8.89 wt% Fe 2 O 3 and many other impurities. 99 Quartz and iron ions are undesirable when zeolites are used as detergents. 3…”
Section: Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…ZSM-5 was synthesized from RM using the dualhydrothermal method [26] as follows. RM was pretreated by an alkaline fusion reaction at 450 °C for 2 h before adding distilled water and stirring for 24 h. The filtrate was separated and dried at 105 °C for 24 h. At molar compositions of 0.2 silicon dioxide (SiO 2 ): 0.004 dialuminium trioxide: 0.04 tetrapropylammonium: 3.6 water, the resulting solid substance was used to prepare ZSM-5 by dissolving it in distilled water.…”
Section: Preparation Of Zsm-5mentioning
confidence: 99%